Evaluation of organized hunting as a management technique for overabundant white‐tailed deer in suburban landscapes - Scott C. Williams; Anthony J. Denicola; Thom Almendinger; Jody Maddock (Wildlife Society Bulletin)
Abstract Hunting has been the primary white‐tailed deer (Odocoileus virginianus) management tool for decades. Regulated hunting has been effective at meeting management objectives in rural areas, but typical logistical constraints placed on hunting in residential and urban areas can cause deer to become overabundant and incompatible with other societal interests. Deer–vehicle collisions, tick‐associated diseases, and damage to residential landscape plantings are the primary reasons for implementing lethal management programs, often with objectives of <10 deer/km2. There are limited data demonstrating that hunting alone in suburban landscapes can reduce densities sufficiently to result in adequate conflict resolutions or a corresponding density objective for deer. We present data from 3 controlled hunting programs in New Jersey and one in Pennsylvania, USA. Annual or periodic population estimates were conducted using aerial counts and road‐based distance sampling to assess trends. Initial populations, some of which were previously subjected to regulated unorganized hunting, ranged from approximately 30–80 deer/km2. From 3 years to 10 years of traditional hunting, along with organized hunting and liberalized regulations, resulted in an estimated 17–18 deer/km2 at each location. These projects clearly demonstrate that a reduction in local deer densities using regulated hunting can be achieved. However, the sole use of existing regulated hunting techniques in suburban areas appears insufficient to maintain deer densities <17 deer/km2 where deer are not limited by severe winter weather. Additional measures, such as sharpshooting or other strategic adjustments to regulations and policies, may be needed if long‐term deer‐management objectives are much below this level. © The Wildlife Society, 2012